Mechanistic Features of the TiO2 Heterogeneous Photocatalysis of Arsenic and Uranyl Nitrate in Aqueous Suspensions Studied by the Stopped‐Flow Technique. Issue 6 (13th January 2016) - Meichtry, Jorge M.; Levy, Ivana K.; Mohamed, Hanan H.; Dillert, Ralf; Bahnemann, Detlef W.; Litter, Marta I.
Abstract: The dynamics of the transfer of electrons stored in TiO2 nanoparticles to As III, As V, and uranyl nitrate in water was investigated by using the stopped‐flow technique. Suspensions of TiO2 nanoparticles with stored trapped electrons (etrap − ) were mixed with solutions of acceptor species to evaluate the reactivity by following the temporal evolution of etrap − by the decrease in the absorbance at λ =600 nm. The results indicate that As V and As III cannot be reduced by etrap − under the reaction conditions. In addition, it was observed that the presence of As V and As III strongly modified the reaction rate between O2 and etrap − : an increase in the rate was observed if As V was present and a decrease in the rate was observed in the presence of As III . In contrast with the As system, U VI was observed to react easily with etrap − and U IV formation was observed spectroscopically at λ =650 nm. The possible competence of U VI and NO3 − for their reduction by etrap − was analyzed. The inhibition of the U VI photocatalytic reduction by O2 could be attributed to the fast oxidation of U V and/or U IV . Abstract : Bait and trap : Stopped flow shows that As V cannot be reduced by the trapped electrons (etrap − ) of TiO2, but increases the rate of the electron‐transfer reaction between O2 and etrap − . As III cannot be reduced by etrap − and inhibits the rate of the reaction between O2 and etrap − . U VI reacts easily with etrap − with U IV formation and is reduced in preference to NO3 − .